Single-cell transcriptomic and spatial analysis reveal the immunosuppressive microenvironment in relapsed/refractory angioimmunoblastic T-cell lymphoma - Mengyan Zhu; Ning Li; Lei Fan; Rongrong Wu; Lei Cao; Yimin Ren; Chuanyang Lu; Lishen Zhang; Yun Cai; Yuzhu Shi; Zihan Lin; Xueying Lu; et al. (Blood Cancer Journal)
Abstract Angioimmunoblastic T-cell lymphoma (AITL) is a kind of aggressive T-cell lymphoma with significant enrichment of non-malignant tumor microenvironment (TME) cells. However, the complexity of TME in AITL progression is poorly understood. We performed single-cell RNA-Seq (scRNA-seq) and imaging mass cytometry (IMC) analysis to compare the cellular composition and spatial architecture between relapsed/refractory AITL (RR-AITL) and newly diagnosed AITL (ND-AITL). Our results showed that the malignant T follicular helper (Tfh) cells showed significantly increased proliferation driven by transcriptional activation of YY1 in RR-AITL, which is markedly associated with the poor prognosis of AITL patients. The CD8+ T cell proportion and cytotoxicity decreased in RR-AITL TME, resulting from elevated expression of the inhibitory checkpoints such as PD-1, TIGIT, and CTLA4. Notably, the transcriptional pattern of B cells in RR-AITL showed an intermediate state of malignant transformation to B-cell-lymphoma, and contributed to immune evasion by highly expressing CD47 and PD-L1. Besides, compared to ND-AITL samples, myeloid-cells-centered spatial communities were more prevalent but showed reduced phagocytic activity and impaired antigen processing and presentation in RR-AITL TME. Furthermore, specific inhibitory ligand-receptor interactions, such as CLEC2D-KLRB1, CTLA4-CD86, and MIF-CD74, were exclusively identified in the RR-AITL TME. Our study provides a high-resolution characterization of the immunosuppression ecosystem and reveals the potential therapeutic targets for RR-AITL patients.